1978
DOI: 10.1073/pnas.75.11.5493
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal effects in human hemoglobin: direct measurement of the dimer-tetramer association constant at partial oxygen saturation.

Abstract: An equilibrium gel permeation technique has been developed for determining as a function of oxygenation state the equilibrium constants for association of hemoglobin subunits. By using this method, the dimer-tetramer constant for human hemoglobin at a partial oxygenation state corresponding to 20% saturation for tetramers has been determined as 3.7 X 106 M-1 (dimers). Under the same conditions the corresponding constant for fully oxygenated hemoglobin is 4.1 X 10&M-1. These results are found to be in good agre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…The major component of the Hp1-1 preparation was a ϳ93-kDa species, consistent with the presence of the Hp1-1 dimer, including ϳ20% mass contribution because of glycosylation; a minor peak at the exclusion volume of the SEC column was assumed to be an aggregate. Hb eluted as a single asymmetric peak, indicative of the well characterized dimer-tetramer equilibrium (24); the measured molecular mass of 57 kDa suggested that the protein was predominantly in the tetrameric state under the experimental conditions. Analysis of a 1:1 (by mass) mixture of IsdH N1 with Hp showed no significant change in the peak elution times or molecular masses as determined by RALS (Fig.…”
Section: N1mentioning
confidence: 99%
“…The major component of the Hp1-1 preparation was a ϳ93-kDa species, consistent with the presence of the Hp1-1 dimer, including ϳ20% mass contribution because of glycosylation; a minor peak at the exclusion volume of the SEC column was assumed to be an aggregate. Hb eluted as a single asymmetric peak, indicative of the well characterized dimer-tetramer equilibrium (24); the measured molecular mass of 57 kDa suggested that the protein was predominantly in the tetrameric state under the experimental conditions. Analysis of a 1:1 (by mass) mixture of IsdH N1 with Hp showed no significant change in the peak elution times or molecular masses as determined by RALS (Fig.…”
Section: N1mentioning
confidence: 99%
“…Characterization of ligand binding properties for the subunits in various stages of assembly, and of the assembly reactions themselves, provides an experimental basis for understanding how subunit interaction brings about the observed alterations in affinity and regulatory properties. For normal human hemoglobin a comprehensive set of thermodynamic properties pertaining to these processes has recently been developed (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). The resulting energetic picture imposes constraints that must be satisfied by any theory proposed to explain the mechanism of cooperative oxygen binding.…”
Section: Introductionmentioning
confidence: 99%
“…THERMODYNAMIC RESOLUTION OF THE LIGAND-LINKED ASSEMBLY FOR HUMAN HEMOGLOBIN A series of recent experimental studies on human hemoglobin (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) has provided an extensive and self-consistent set of thermodynamic properties pertaining to (a) the linkage between dimer tetramer association and oxygen binding, (b) the effects of pH and chloride on the oxygenation linked dimer-tetramer reactions, (c) the properties of isolated chains, including their ligand binding and self-association reactions, and (d) the reconstitution of functional hemoglobin tetramers from the constituent subunits. The results summarized here will focus mainly upon the processes of categories a and b.…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, once the glucose 6-phosphate is attached, the equilibrium subunit distribution of dimer and tetramer becomes refractory to the binding of either 02 or CO ligands. These results, taken together with the established linkage between subunit dimer-tetramer equilibrium and 02 binding for human haemoglobin [1,8], are not consistent with the glucose 6-phosphate moiety competing for the same binding site as does 2,3-bisphosphoglycerate on this macromolecule [3,5,20].…”
Section: Discussionmentioning
confidence: 60%
“…Studies suggest that the covalent attachment of D-glucose 6-phosphate to human haemoglobin may be functionally analogous to the binding of 2,3-bisphosphoglycerate [3,5]. That hypothesis would suggest that glucose 6-phosphate should stabilize the deoxy or tetramer form of the dimer-tetramer subunit assembly of haemoglobin [6,7,8]. Direct measurement of the dimertetramer equilibria of glucophosphorylated haemoglobin would establish a basis on which to support or reject the hypothesis proposing homology between the interactions of 2,3-bisphosphoglycerate or glucose 6phosphate with human haemoglobin.…”
Section: Introductionmentioning
confidence: 99%